Correlation Between Hand Grip Strength and Glycemic Control Among Saudi Children with Chronic Type 1 Diabetes Mellitus (T1DM) (The Review of Diabetic Studies, 2023)
Objectives: We aimed to study the correlation between the hand grip strength as an indicator of the musculoskeletal affection and the degree of glycemic control in Type 1 Diabetic pediatric patients. Methods: Cross-sectional interventional study conducted among children having chronic T1DM recruited from the pediatric diabetes clinic at King Fahd hospital of the University, Saudi Arabia, they were divided into 3 groups according to their HbA1c level to well controlled, fairly controlled and poorly controlled. Anthropometrics measure taken then handgrip strength for both dominant and nondominant hands were measured using valid and reliable digital JAMAR PLUS hand dynamometer, data collection was performed according to the American Society of Hand Therapists (ASHT) guidelines. Results: Total of 150 patients, aged 5-18 years, with 56% females and 44% males, two third of them were poorly controlled. Well controlled group showed better hand grip strength than the other 2 groups however it was not statistically significant. Conclusions: The handgrip strength in Type 1 DM children is affected by the degree of the glycemic control and it might give a clue of early musculoskeletal functional derangement by the effect of chronic hyperglycemia in these affected children.